Effects of the Breeding Strategy Beef-on-Dairy at Animal, Farm and Sector Levels - Rana Hamas Ahmed; Christin Schmidtmann; Julius Mugambe; Georg Thaller (Animals, 2023)
The decline in farm revenue due to volatile milk prices has led to an increase in the use of beef semen in dairy herds. While this strategy (“Beef-on-dairy” (BoD)) can have economic benefits, it can also lead to unintended consequences affecting animal welfare. Semen sale trends from breeding organizations depict increasing sales of beef semen across the globe. Calves born from such breeding strategies can perform better when compared to purebred dairy calves, especially in terms of meat quality and growth traits. The Beef-on-dairy strategy can lead to unintentional negative impacts including an increase in gestation length, and increased dystocia and stillbirth rates. Studies in this regard have found the highest gestation length for Limousin crossbred calves followed by calves from the Angus breed. This increase in gestation length can lead to economic losses ranging from 3 to 5 US$ per animal for each additional day. In terms of the growth performance of crossbred animals, literature studies are inconclusive due to the vast differences in farming structure across the regions. But almost all the studies agree regarding improvement in the meat quality in terms of color, fiber type, and intra-muscular fat content for crossbred animals. Utilization of genomic selection, and development of specialized Beef-on-dairy indexes for the sires, can be a viable strategy to make selection easier for the farmers.